Fibroblast growth factor 23 (FGF-23) is an early predictor of mortality in patients with cardiac arrest - Spaich, Sebastian; Zelniker, Thomas; Endres, Philipp; Stiepak, Jan; Uhlmann, Lorenz; Bekeredjian, Raffi; Chorianopoulos, Emmanuel; Giannitsis, Evangelos; Backs, Johannes; Katus, Hugo; Preusch, Michael (Resuscitation, 2016)
Background - Post-cardiac arrest management has seen significant advances with profound improvements in survival and neurologic outcome. However, early prognostication after return of spontaneous circulation remains most challenging. Biomarkers have evolved as helpful tools in identifying patients who are at increased risk of adverse outcome. While fibroblast growth factor 23 (FGF-23) has recently emerged as a promising predictor of mortality in patients with cardiogenic shock, its role in risk stratification in post-resuscitation management remains unresolved. - Methods - This study included 90 patients who had been resuscitated and transferred to the ICU of the University Hospital Heidelberg. Survivors and non-survivors were retrospectively analyzed for known prognostic biomarkers as well as FGF-23 serum levels 24h and 72h post cardiac arrest (CA). - Results - FGF-23 levels were significantly elevated in non-survivors compared to survivors. ROC analysis of FGF-23 levels at 24h and 72h post CA yielded an AUC of 0.759 and 0.726, respectively, for prediction of overall survival after 6 months. FGF-23 levels remained as significant prognosticators after adjusting for age, renal function, and initial cardiac rhythm. FGF-23 levels did not show significant differences in patient outcome after stratification for cardiac origin of CA or left ventricular dysfunction. Furthermore, FGF-23 levels were moderately predictive of poor neurologic outcome in ROC analysis on day 1 and day 3 post CA with an AUC of 0.738 and 0.687, respectively. - Conclusion - This study demonstrates elevated FGF-23 serum levels to be potentially helpful in prediction of mortality and poor neurological outcome as early as 24h post cardiac arrest.
Available online 30 November 2015
Gesehen am 12.05.2020